An efficient pseudo-seven component reaction for the synthesis of fully-substituted furans containing pseudopeptide based on the union of multicomponent reactions. Issue 3 (16th January 2020) - Nazeri, Mohammad Taghi; Mohammadian, Reza; Farhid, Hassan; Shaabani, Ahmad; Notash, Behrouz
Graphical abstract: Highlights: Pseudo -seven component reaction base on the union of multicomponent reactions. Synthesis of fully-substituted furan derivatives containing pseudopeptidic groups. The synthetic protocol provides up to ten novel bond formations. Abstract: An atom, step, and energy economic approach based on the union of multicomponent reactions (MCRs) is reported to create higher-order MCRs with unique possibilities for complexity generation of fully-substituted furan derivatives containing pseudopeptidic groups. The unprecedented seven component reaction resulting from implementation of this strategy, provides very complex and valuable scaffolds with several diversity points and up to ten novel bond formations in a one-pot process. This new protocol has proven to be an appropriate green method for the synthesis of biologically relevant furans with extraordinary functional-group from readily available starting materials.